Conversor CA-CC Flyback trifásico para iluminação pública utilizando LEDS de potência - Mendonça, Marcel Ribeiro (2014)
This paper presents the development of a three-phase AC-DC flyback converter with power factor correction without electrolytic capacitor, applied in street lighting using power LEDs. A review of some of the main topologies in the literature applied on LED lighting is performed. Furthermore, the using of an AC-DC converter with three-phase power supply, in order to withdrawal the electrolytic capacitors of the converter, is also proposed. The lifetime and reliability of AC-DC converters may be increased removing the electrolytic capacitors, considering that its lifetime has strong influence of the operating temperature. A study about three-phase AC-DC converters derived from the buck-boost topology is also performed, and a three-phase topology with one switch is analyzed. A prototype of this topology is developed, and the simulation and experimental results evidence the feasibility of using this technology in AC-DC converter LEDs. The prototype has an output power of 54 W, with power factor up to 0.99 and efficiency up to 77%, using low cost commercial ferrite core, and depending on the operating conditions. This prototype can operate in full-range of input voltages and also has a peak current control strategy, which reduces design costs due the using of a low cost controller.